Changes of Marukh Glacier from 1945 to 2011 - S. S. Kutuzov; I. I. Lavrentiev; Yu. Ya. Macheret; D. A. Petrakov (Лëд и снег)
Field studies have been carried out in summer 2011 at Marukh Glacier located in western part of the Northern Caucasus. The studies included ground-based radio-echo sounding measurements at a frequency of 20 MHz and glacier surface elevation survey using a dual frequency differential GPS receiver. Changes of volume and surface area of the glacier for the period 1945–2011 have been estimated using aerial photo, satellite images and topographic maps analysis. It is founded that Marukh Glacier is retreating and has reduced its surface area by 17% for the past 66 years. Glacier volume is 0,276 km³ in 2011 and has decreased by 0,06 km³ since 1967.